THE EFFECT OF MOTIVATION AND WORK ENVIRONMENT ON THE PERFORMANCE OF HOTEL EMPLOYEES, MURIA SEMARANG - Arta Adi Kusuma (Jurnal Ekonomi, 2021)
The population in this study were all 115 employees of Hotel Muria Semarang. The sample was determined by proportional random sampling technique, with 53 respondents as respondents. The data collection method used is a questionnaire (questionnaire) and documentation method. The data analysis method used in this research is the percentage description analysis method and multiple linear regression. Based on the results of the study, it was obtained that the multiple linear regression equation = 23.857 + 0.180 X1 + 0.94 X2. By using SPSS 16 the results of the F test hypothesis show F count = 16,646 with a significance value = 0.000 <0.05 which means H3 which reads "There is a significant influence of motivation and work environment on employee performance at Hotel Muria Semarang" is accepted. Meanwhile, from the partial hypothesis test (t test) it is obtained that the t count of the motivation variable is 2,619, the t count of the work environment variable is 2,207 where the probability is less than 0.05 then the hypothesis is accepted. The coefficient of determination (Adjusted R2) is 0.376, this means that 37.6% of the employee performance of Hotel Muria Semarang is influenced by motivation and work environment, while the rest is influenced by other variables that are outside the variables studied in this study. The conclusion is that motivation is in the good category, the work environment is in the good category, and the performance of the employees of Hotel Muria Semarang is in the good category. Motivation has an influence on employee performance with a contribution of 12.04%. The work environment has an influence on employee performance with a contribution of 8.88%. Motivation and work environment together have an influence on employee performance with a contribution of 37.6%. Suggestions that can be given in this study are indicators of the need for security, namely the absence of a better future guarantee from the company. It is hoped that the need for security can be overcome, such as by having a pension fund after the work period is over or an old-age guarantee. The indicators of social needs are the lack of interaction between employees at work and the indifferent attitude between employees. It is hoped that social needs can be overcome by the company holding tours or recreation with employees so that relations between employees are closer, creating working groups for employees. From the work environment variables, the weakness in the lighting indicator